Measurements and Calculations of Protein Intramolecular Vibrations in the THz Range - Niessen, K. A.; Snell, E.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
We report the calculations and measurements of intramolecular vibrational modes and their dependence on inhibitor binding in the THz range. We see an increase in anisotropic THz absorption at low frequency with inhibitor binding in both the measurements and calculations. This surprising result suggests an increase in flexibility with binding. We will discuss the possible reasons for this discrepancy.
ISI Document Delivery No.: BF0IL Times Cited: 0 Cited Reference Count: 13 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Balog E, 2004, PHYS REV LETT, V93, DOI 10.1103/PhysRevLett.93.028103 Best RB, 2012, J CHEM THEORY COMPUT, V8, P3257, DOI 10.1021/ct300400x BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 BRUCCOLERI RE, 1986, BIOPOLYMERS, V25, P1767, DOI 10.1002/bip.360250916 CHEETHAM JC, 1992, J MOL BIOL, V224, P613, DOI 10.1016/0022-2836(92)90548-X Dong J, 1999, ACTA CRYSTALLOGR D, V55, P745, DOI 10.1107/S0907444998016047 Guo JN, 2014, BIOCHEMISTRY-US, V53, P2855, DOI 10.1021/bi500238q Hammes-Schiffer S, 2006, ANNU REV BIOCHEM, V75, P519, DOI 10.1146/annurev.biochem.75.103004.142800 Henzler-Wildman KA, 2007, NATURE, V450, P838, DOI 10.1038/nature06410 Jo S, 2008, J COMPUT CHEM, V29, P1859, DOI 10.1002/jcc.20945 PERUTZ MF, 1970, NATURE, V228, P726, DOI 10.1038/228726a0 TEETER MM, 1990, J PHYS CHEM-US, V94, P8091, DOI 10.1021/j100384a021 Niessen, Katherine A. Snell, Edward Markelz, A. G. Irmmw-thz Proceedings Paper 39th International Conference on Infrared, Millimeter, and Terahertz waves (IRMMW-THz) Sep 14-19, 2014 Tucson, AZ THORLABS, Tydex, TOPTICA Photon, Bruker, Gentec EO, Lake Shore Cryotron, Ekspla, Zomega, TeraSense, Insight Product, Emcore, QMC Instruments, TeraView, NeaSpec, Advantest, MenloSystems, Traycer, Microtech Instruments Inc, LongWave Photon, Virginia Diodes Inc, ASU, MTT S, Journal Infrared Millimeter & Tera Hertz Waves, Tera Hertz Sci & Technol, Army Res Off Snell, Edward/G-2055-2018 Snell, Edward/0000-0001-8714-3191 345 e 47th st, new york, ny 10017 usa 2162-2027
Keywords: charmm